SYNTHESIS OF MULTICULTURAL EDUCATION AND CARE OF DISTRICT CULTURE IN PESANTREN (EDUCATION IN TMI AL-AMIEN PRENDUAN SUMENEP MADURA INDONESIA) - Iwan Kuswandi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2016)
Society of Indonesia should live peace in diversity without leaving regional values. pesantren as education institute has important role in integrating of two items. pesantren of TMI Al-Amien Prenduan is one of pesantren that has strategies in education of multicultural to students (santri), without leaving regional education. It can be witnessed that students’ room should stay in community that come from in any districts over Indonesia, it is as education of multicultural (they don’t stay in one community). In addition, it is to keep away ethnic fanaticism and tribal, so students should obligated to communicate Arabic, English and Indonesia in daily life. In curriculum, in TMI Al-Amien Prenduan is taught religion confrontation and the Islamic School of Doctrine of jurisprudence (madzhab fiqh), to keep away fanaticism in being religion and Islamic School of Doctrine. But, TMI Al-Amien Prenduan holds student entertainment in a week to continue regional cultural wealth that packed into consulate dynamic event (each district over Indonesia), such as fairy tale folklore competition ect. In addition, the students is obligated to publish month bulletin in Madura that contained of history, legend in journalistic each districts.